Strategic Management Towards Learning Organization in Agricultural Cooperative - Saengwang, Chutiban (The Journal of Development Administration Research, 2021)
The purposes of this research were to determine: 1) the factors of learning organization, and 2) the guidelines for strategic management towards learning organizations in agricultural cooperatives. The population used in this research consisted of agricultural cooperative with 210 cooperative learning centers nationwide. The sample group composed of 136 cooperatives by used Krejcie and Morgan table. The respondents were managers and administrators of learning centers in the cooperative with the total of 272 respondents. The research tool was a semi-structured interview, Opinionnaires and guidelines questionnaires for strategic management towards learning organizations in agricultural cooperatives of experts and specialists. The statistics for analyze the data were frequency, percentage, arithmetic mean, standard deviation, and exploratory factor analysis. The findings of this research were as follows: 1. The factors of a learning organization composed of 6 components: 1) the learning dynamics, with19 variables, 2) information technology and innovation, with 16 variables, 3) knowledge management, with 8 variables 4) organizational transformation, with 11 variables, 5) knowledge enhancement for personnel, with 7 variables, and 6) participatory management, with 6 variables. 2. The guidelines for strategic management towards learning organizations in agricultural cooperatives from experts and specialists found 67 approaches and synthesized it into the theory of Kinicki and Williams, which mentioned about the Strategic-Management Process of 5 steps: 1) establish the mission, vision, and values statements, 2) assess the current reality, 3) formulate corporate, business, and functional strategies, 4) execute the strategy, 5) maintain strategic control: the feedback loop.